Future Studies of Kurdistan Province Development: Issues and Challenges - Farnaz Izadi; Atefeh Ahmadi; Farzin Charehjoo (تحقیقات کاربردی علوم جغرافیایی)
Future study as an emerging knowledge is the evolutionary form of strategic planning. This knowledge has been used purposefully in recent years to meet the uncertainty and complexity of various dimension of issues and to designing the future of systems. In this regard, Kurdistan province in western Iran, despite the potential and actual capabilities, has not achieved the development appropriate with capacities and there are many structural problems in achieving this purpose. In this regard, the present study has examined the problems and challenges of lack of development in Kurdistan province with a descriptive-analytical and future study approach. The method of data collection is a survey and documentary studies. The problems and challenges and their effects on the development of the province have been identified to achieve results based on a semi-structured interview from elites and experts. MIC MAC software, environmental scanning method, and system analysis are used to analyzing the data. The results of the research in assessing the extent and the way of influencing of issues and challenges on each other and on the future status of development in Kurdistan province, respectively in the direct and indirect  effectiveness and impressionability, indicates that water crisis, poverty, lack of development of industry, unbalanced tourism and animal husbandry, environmental degradation and lack of access to health services, unemployment, and improper management of water facilities play a major role in the future of development in Kurdistan province